PROVISION OF SUGAR-SALT SOLUTION AS AN EFFORT TO DECREASE THE LOSS OF PIG CARCASS COMPONENTS BECAUSE OF SLAUGHTERING DELAY - Tirta Ariana, I.N.; Saka, I Kt.; Harya Putra, D.K.; Suyadnya, I Pt. (E-Journal Of Animal Science Udayana University; Vol 1, No 1, Tahun 2012)
Become of the aims of this study was to determine the effects of sugar-salt solution given to pigs during periods of slaughtering delay as an effort to decrease weight losses of main physical components of their carcasses. The study used randomized complete block design and a 3 x 4 factorial treatment array. The treatments were three levels of sugar-salt solution, i.e. g0 (had no access to the sugar-salt solution or provided with plain water only), g1 (treated with 150 g sugar + 15 g salt solution), and g2 (treated with 300 g sugar + 30 g salt mixture), and four levels of slaughtering delay i.e.  l0 (without slaughtering delay), l1 (one day of slaughtering delay), l2 (two days of slaughtering delay), and l3 (three days of slaughtering day). The sugar-salt mixture was diluted in 1 litter of water. Results of the study showed that there was no interaction between provision of the solution and slaughtering delay on weight of main physical components (meat, bone and fat) of the carcass. As a separate factor, however, provision of the solution or slaughtering delay alone has significantly (P<0.05) affected weight of the carcass components. Prolonged slaughtering delays significantly lowered (P<0.05) weights of dissected meat and subcutaneous fat ranging from 0.9 to 13.5%, and from 14.1 to 29.3%, respectively. Weights of bone, inter-muscular fat, and skin, however, were not significantly affected (P>0.05) by the slaughtering delays. Moreover, provision of the sugar-salt solution significantly (P<0.05) decreased the weight losses of meat and subcutaneous fat so that their weights were higher by 21.6 and 12.9% compared to control, respectively. But, the solution had no affect (P>0.05) on bone, intermuscular fat, and skin weights. It could be concluded that the provision of sugar-salt solution is a importen attempt to reduce losses of meat subcutaneous fat of pig carcass when fewcess have to be delayed.
Keywords: pig, sugar-salt solution, slaughtering delays, and physical components of the carcass.